HR analytics a roadmap for decision making: case study - Brahim Jabir; Noureddine Falih; Khalid Rahmani (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In the socio-economic world, the human resources are in the most top phase of the enterprise evolution. This evolution began when the arithmetic, statistics are applicable over a vast of opportunities and used to identify problems and support decision. However, analytics has been emerged to provide predictions and understand the people performance based on available data.In light of this vast amount of information, human resources services need to deploy a predictive management model and operating system of analytics that can be an efficient and an instead solution that can respond to the gaps of the traditional existing ones and facilitate the decision making. In this paper, we present a literature review of this HR analytics concept and a case study concerning the impact of interventions using an analytics solution.